Minimally invasive epicardial left-ventricular lead implantation and simultaneous left atrial appendage closure - Petersen, Johannes; Alassar, Yousuf; Yildirim, Yalin; Tönnis, Tobias; Reichenspurner, Hermann; Pecha, Simon (Frontiers in Cardiovascular Medicine, 2023)
Background Atrial fibrillation (AF) is common in patients with heart failure resulting in a high prevalence of AF in patients receiving CRT implantation. In patients, unsuitable for transvenous LV-lead implantation, epicardial LV-lead implantation represents a valuable alternative. Epicardial LV-lead placement can be achieved totally thoracoscopical or via minimally invasive left lateral thoracotomy. In patients with atrial fibrillation, concomitant LAA clipping is feasible via the same access. Therefore, the aim of our study was the analysis of safety and efficacy of epicardial LV lead implantation and concomitant LAA clipping via minimally invasive left-lateral thoracotomy. Methods Between December 2019 and March 2022, 8 patients received minimally invasive left atrial LV-lead implantation with concomitant LAA closure using the AtriClip. Transesophageal echocardiography (TEE) was performed to intraoperatively guide and control LAA closure. Results Mean patients age was 64±11.2 years, 67% were male patients. Minimally invasive left-lateral thoracotomy was used in 6 patients while a totally thoracoscopic approach was performed in 2 cases. Epicardial lead implantation was successfully performed in all patients with good pacing threshold (mean 0.8±0.2 V) and sensing values (10.1±2.3 mV). Posterolateral position of the LV lead was achieved in all patients. Furthermore, successful LAA closure was confirmed during TEE in all patients. No procedure-related complications occurred in any of the patients. Two patients additionally received simultaneous laser lead extraction during the same procedure. Complete lead extraction was achieved in both patients. All patients were extubated in the OR and had an uneventful postoperative course. Conclusion Our study highlights a novel treatment approach for patients with atrial fibrillation and the necessity of epicardial LV leads. Placement of a posterolateral LV lead position with concomitant occlusion of the left atrial appendage via a minimally-invasive left-lateral thoracotomy or even a totally thoracoscopic approach is safe and feasible with superior cosmetic result and complete occlusion of the left atrial appendage.